Analisis Pola Konsumsi Daging Ayam Broiler Dan Ayam Lokal Pada Masyarakat: Kajian Faktor Harga Dan Preferensi Konsumen Di Distrik Liquiça Dan Aileu, Timor-Leste - Pereira, Benigno; Coelho, Agotinho; Rodriques, Julião Henriques; Pinto, Mateus (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the consumption patterns of imported broiler chicken and local chicken in Timor-Leste by emphasizing the influence of price, consumer preferences, and socio-cultural factors in Liquiça and Aileu. A mixed-methods approach was employed through household surveys involving 290 respondents and key informant interviews, with data analyzed using descriptive statistics, binary logistic regression, factor analysis, and conjoint analysis. The results indicate that communities in Liquiça tend to prefer imported broiler chicken due to affordability and market availability, while communities in Aileu show stronger preferences for local chicken driven by cultural values and perceived quality. Price emerged as the primary determinant (45%) of consumption decisions; however, cultural attachment maintained relatively strong demand for local chicken. Geographic location, cultural values, and taste preferences were found to significantly influence poultry consumption patterns. These findings provide an empirical foundation for region-based food policy development to strengthen sustainable food security in Timor-Leste.